Relationship between changes of rules and the design of training - Etaati, A. (International Journal of Wrestling Science, 2013)
Research indicates that the ignorance of a majority of coaches with exigencies of the FILA rules and subsequent rule changes has been the most important reason for the International Olympic Committee's (IOC) recommendation for elimination of wrestling from the 2020 Olympic Program. On the other hand, properly educating and updating coaches, wrestlers and referees on the rules and ways to implement them would ensure a return of beauty, attraction and fairness to wrestling competitions, thus guaranteeing reinstatement of the oldest branch of sport in the Olympics. Change in the educational system in proportion with the wrestling spirit would be so advantageous, that it would motivate the international audio-visual media, i.e. TV, press and internet, to cover and reflect wrestling alongside football events. In another words, changes in rules and the design of training - that is the core of the research at hand - would reflect the Olympic Games' motto "Faster, Higher, Stronger". Highlights of the researcher's suggestions are as follows: Preparing wrestlers for 5-6 competitions/day; prioritizing offensive over defensive wrestling; designing training in tune with mandates of rules; designing competition-specific training; emphasize the importance of the zone and develop the necessary tactics to make wrestling in the zone more competitive; designing training assimilated with competition conditions; preventing wrestlers from refraining to do helpful exercises; explaining to wrestlers the difference between fleeing from mat and fleeing from enforcement of techniques; designing 15- and 30-second speed and power training to raise speed, power and resistance of wrestlers; Avoiding partial practice of techniques; enhancing effective span of exercises; including upper-body techniques in trainings; teaching wrestlers which techniques to use when being ahead or behind; teaching wrestlers logical offense/defense to avoid caution for passivity; designing training specifically for implementing 3-/5-point score techniques both in FS/GR; building a link with referees as executors of rules; Learning details of the Challenge Law and applying it in best possible manner; getting wrestlers prepared for changing tactics under special conditions; banning wrestlers from play of fault techniques both in training and competitions; dividing competition periods to ensure beautiful wrestling .